Which localization method is optimal in ESWL: fluoroscopy or ultrasonography? - Dursun Baba; Necati Ekici; Arda Taşkın Taşkıran; Yusuf Şenoğlu; Alpaslan Yüksel; Ekrem Başaran; Mehmet Ali Özel; Ahmet Yıldırım Balık (BMC Urology)
Abstract Background Urinary stone disease is a common urological disorder, particularly among middle-aged individuals. Extracorporeal Shock Wave Lithotripsy (ESWL) is often the first-line treatment for kidney and ureteral stones. Traditionally, fluoroscopy is used for stone targeting in ESWL, but it exposes patients and clinicians to radiation and cannot visualize non-opaque stones. Ultrasonographic targeting eliminates these issues. This study compares the advantages and disadvantages of fluoroscopy and ultrasound-targeted ESWL. Methods At Düzce University Hospital, 100 patients with radio-opaque stones indicated for ESWL between February 2023 and February 2024 were divided into two groups. Group A underwent ESWL with fluoroscopic targeting, while Group B used ultrasonographic targeting. Patient demographics, stone size (measured by CT), and stone locations were recorded. The number of shocks per session, energy intensity (kV), and fluoroscopy time were noted for Group A. One week after each ESWL session, patients were evaluated by ultrasound or direct radiography. Success was defined as being stone-free or having ≤ 4 mm asymptomatic residual stones after up to four sessions. Failure was defined as no results after two sessions or the need for additional treatment. Results The procedure success rate was 66% for men and 78% for women, with no statistically significant gender difference (p > 0.05). Stone locations were similar in both groups. Success rates were 66% in Group A and 74% in Group B, with no significant difference (p > 0.05). Successful procedures were associated with an average patient weight of 76.6 kg, stone size of 8.9 mm, and total energy of 12.2 kV, with significant differences compared to unsuccessful procedures (p < 0.04, p < 0.04, p < 0.001, respectively). No significant differences were found between Group A and Group B in terms of age, height, BMI, stone density (HU), and number of sessions (p > 0.05). Conclusion Ultrasonography is as effective as fluoroscopy for imaging and focusing during ESWL treatment. It enhances the success of ESWL for non-opaque stones and reduces radiation exposure disadvantages.